The history of the exotic industry in Texas - Seale, Charly, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
The beginning of the Exotic Industry in the United States and its effect on the rural economy.
Conservation through commerce in the United States and the exotic industry's economic impact on rural USA
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.